Stomach Content Analysis of Thynnichthys thynnoides from the Pinang Luar Oxbow Lake, Buluhcina Village, Siak Hulu Subdistrict, Kampar Regency, Riau Province - Kika Ananda; Ridwan Manda Putra; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Thynnichthys thynnoides is commonly inhabit the Pinang Luar Oxbow Lake. Information of the stomach content of this fish, however is limited. To understand the stomach content and its relation to size, sex and environmental condition, a research has been done on March to April 2016. There were 3 stations, around inflows of the Kampar River (St 1), at the middle of the lake (St 2), and the rear end of the lake (St3). Sampling was conducted 4 times, twice/month. Type of food present in the stomach of fish was analyzed and the PI (Preponderance Index) was calculated. There were 149 fishes captured and all of the fish were used in this study. Results shown that T. thynnoides is a plankton feeder, and there was no main food, but in general Cyanophyceae is the highest (PI37%) and the supplementary food was Protozoa (0.02%). In small fish, Euglenophyceae was 37%, while in the large fish Cyanophyceae was 39%. There are no differences of food type in male and female fishes.Keywords: Thynnichthys thynnoides, Stomach Content Analysis,Preponderance Index, Pinang Luar Oxbow Lake